'The danger of a single story:' a reflection on institutional change, voices, identities, power, and outcomes. Issue 2 (3rd April 2019) - Huang Hoon, Chng; Mighty, Joy; Roxå, Torgny; Deane Sorcinelli, Mary; DiPietro, Michele
ABSTRACT: What role does academic development have to play in responding to radical cultural shifts in the global landscape? Whose voices and identities are contributing to institutional change? This reflective essay encompasses the perspectives of the four international panellists in the opening plenary of the International Consortium for Educational Development (ICED) 2018 conference in Atlanta, Georgia, USA – Torgny Roxå on ideologies; Chng Huang Hoon on agency and empowerment; Joy Mighty on voices and identities; and Mary Deane Sorcinelli on evidence and outcomes. These perspectives set the stage for the conference, and, brought together in this paper now, they address key conference themes, offer coordinates for reflection, and pose further questions about our profession.